The volcanic stratigraphy and metallogeny of Notre Dame Bay, Newfoundland - Dean, Paul L., 1950- (1978)
Thesis (M.Sc.)--Memorial University of Newfoundland, 1978. Earth Sciences Bibliography: leaves [179]-193.